Cloud first – tackling the security challenges. Issue 1 (January 2018) - Nicholson, Dave
Abstract : Organisations of all shapes and sizes and in every sector of our economy are increasingly drawn to the idea of moving their data and applications to the cloud. When one looks at the huge array of practical benefits that can be achieved by doing so, this growing interest and escalating uptake is hardly surprising. After all, by migrating their resources to the cloud, organisations can achieve enhanced scalability, a significant reduction in operating costs, greater collaboration and document control and provide ubiquitous access to their applications. Organisations are increasingly drawn to the benefits of the cloud. And we are seeing many of them adopting a 'cloud first' strategy. This does not mean, however, that organisations no longer have security issues to confront or data management concerns to address. This new cloud-focused IT landscape brings with it threats from both external and internal sources, adding to the pressure placed on the organisation's security and networking teams, explains Dave Nicholson of Axial Systems.